ANALISIS SEMI-HISTORIS UNSUR-UNSUR BAHASA ARAB DALAM BAHASA INDONESIA - Mukhibat, Mukhibat (IAIN Ponorogo, 2015)
Abstract: The history recorded that the Arab traders went to Indonesia not only to spread the religion, but also to enrichthe Indonesian words. Arabic has a large impact and high integration in Indonesian. As a result, there are many Arabic words/ terms that lost their original forms. Thus, it is not easy to determine whether the words/ terms come from the Arabic or Indonesian original elements, unless in-depth research has been conducted. Hence, with a semi-historical and grammatical approach, this current research attempted to investigate that the language changed at all levels of linguistics features, both phonology, morphology, syntax, semantics and lexicon was due to historical factors which were closely related with the development of language. The absorption of Arabic elements in Indonesian wasbasing on material deprivation, as a variation, enhancing diversity, grandeur, and religious reasons. The process of absorption was through the direct and indirect method. The direct absorption process meant that Indonesian absorbed words from Arabic without going through an arbiter language. Meanwhile, the indirect absorption dealt with the process in which Indonesian absorbed the Arabic words through other languages, i.e., regional languages. The absorption process resulted in huge changing fromArabicwordsinto Indonesian, andthesehave become essential sources for educators in teaching Arabic. One of methods that can be developed is a Kognat (cognate method), because this method utilizes Indonesian words which are similar to Arabic.